Recalcitrant Pseudomonas Aeruginosa Keratitis with Hyphaema - Chan, Amy (Case Rep Ophthalmol, 2021)
PURPOSE: To report a case of recalcitrant pseudomonas keratitis with a rare presentation of hyphaema. OBSERVATION: A 45-year-old female was noted to have contact lens-related pseudomonas keratitis with hyphaema. The organism was refractory to multiple antibiotics and only responded to Tazocin eye drops. CONCLUSION AND IMPORTANCE: Hyphaema is a rare presentation in bacterial keratitis and could represent infection with an especially virulent organism. Use of Aspirin could precipitate hyphaema in infective keratitis. Alternative antibiotic choices such as Tazocin, colistin, meropenem, and imipenem can be considered when standard therapy is ineffective for multidrug-resistant Pseudomonas keratitis.